W-mass prediction in the complex NMSSM - Dao, Thi Nhung; Gabelmann, Martin; Muehlleitner, Margarete (Communications in Physics, 2025)
In this work, we present our recent calculation of the \(W\) boson mass in the complex Next-to-Minimal Supersymmetric Standard Model (NMSSM), which includes all state-of-the-art higher-order supersymmetric corrections to \(Δ r\). In particular, we include the full one-loop corrections and the leading and sub-leading two-loop corrections \(\mathcal{O}(α + α_tα_s + \left(α_t+α_λ+α_κ\right)^2)\) from the \(ρ\) parameter. We show some numerical investigations of the dependence of \(Δρ\) on the renormalization schemes and of the dependence of \(M_W\) on some selected parameters. We also discuss comparisons between some public tools which compute \(M_W\) in the NMSSM. Finally we present a new version of the public Fortran code, {\tt NMSSMCALC}, including a new \(M_W\) prediction.